Development of deft amplification refractory mutation sequencing system (ARMSS) for discriminating Pilos antler based on a short cytochrome b (Cytb) gene. (3rd March 2016) - Wang, Xueyong; Xu, Guojie; Liu, Chunsheng; Huang, Luqi; Zhao, Baosheng; Ren, Xiaolei; Fu, Xiaorui; Ren, Guangxi; Liu, Siqi
Abstract: Pilos antler (Lu-Rong in Chinese) is a famous traditional medicine in China. Many adulterants have been discovered in Chinese markets in recent years. However, few DNA-based methods are effective for discrimination of this DNA-degraded animal medicine. Here, novel and deft amplification refractory mutation sequencing system (ARMSS), integrating the advantages of the amplification refractory mutation system (ARMS) and the short DNA barcode, was first developed to discriminate Pilos antler from its adulterants. We aimed to provide a new sight and inspiration for deft detection. The results showed that developed ARMS achieved strong specificity and high sensitivity in rapid identification, while the short Cytb gene was of excellent identification power in terms of accurate identification, which suggested that ARMSS successfully integrated the advantages of the ARMS and short DNA barcode, and that it was useful for deft detection. Our study determined that the deft ARMSS could be the well candidate for discrimination of Pilos antler, as well as be a valuable tool for deft identification of Chinese medicine.